Transformative School Leadership in Developing Teacher Professionalism in Islamic Boarding Schools of Southern Thailand: A Multiple Case Study - Khoiree Sawa; Fatah Syukur; Abdul Wahid (Journal of Counseling, Education and Society, 2025)
This study aims to analyze the application of transformative school leadership in developing teacher professionalism in Ma'had Darul Maarif and Ma'had Al-Bitsat Ad-Diniah, Southern Thailand, as well as identify the factors that support and hinder its implementation and its implications for teacher professionalism. The research uses a qualitative approach with a multicase case study design to gain an in-depth understanding of leadership practices in the context of Islamic education. Data is collected through in-depth interviews, participatory observations, and document analysis, then analyzed thematically through a process of coding, categorization, and interpretation in a repetitive manner until thematic saturation is achieved. The results of the study show that transformative school leadership is applied through three main dimensions, namely the transformation of the vision of Islamic education, the professional empowerment of teachers, and the strengthening of organizational culture based on Islamic values. The head of ma'had plays the role not only as an administrative leader, but also as a murabbi who builds collective commitment, guides the development of teachers' competencies, and integrates modern professionalism with Islamic spiritual values. The successful implementation of leadership is supported by a strong institutional identity, collaborative work culture, and support for the Muslim community, while limited resources, unstructured professional development systems, and the demands of modern social and educational change are major challenges. Transformative leadership also has implications for improving teachers' pedagogic competence, strengthening professional identity as Islamic educators, and developing a culture of learning innovation that is still based on Islamic values. This research contributes by offering a transformative school leadership conceptual model that integrates managerial, professional, and spiritual dimensions as a contextual strategy to develop teacher professionalism and strengthen the sustainability of Islamic education in minority Muslim communities.